Passivity-Based Control Strategy With Improved Robustness for Single-Phase Three-Level T-Type Rectifiers - Komurcugil, Hasan; Bayhan, Sertac; Malinowski, Mariusz (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
A passivity-based control (PBC) strategy with improved robustness for single-phase three-level rectifiers feeding resistive and constant power loads (CPLs) is proposed. It is shown that the control of the rectifier can be achieved if the damping injection is applied to the grid current only. In this case, the knowledge of load resistance is required in the computation of reference grid current amplitude. Since the output voltage and load current are dc quantities, the load resistance can be estimated easily. Then, the amplitude of the reference grid current is calculated from the power balance equation of the rectifier. The transfer function from reference grid current to actual grid current is derived. The derived transfer function is analyzed under variations in the filter inductance. The results reveal that the proposed PBC offers strong robustness to variations in the filter inductance when a suitable damping gain is selected. The performances of the proposed PBC strategy under undistorted and distorted grid voltage as well as, variations in inductor are investigated via experimental studies during steady-state and transients caused by the resistive load and CPL changes. In all cases, the output voltage is regulated at the desired value, and grid current tracks its reference.
Keywords: Rectifiers; Damping; Switches; Voltage control; Robustness; Resistance; Mathematical model; Passivity-based control; damping injection; three-level T-type rectifier; constant power load